A Two-Level Constant-Elasticity-of-Substitution Production Function - Sato, K. (Review of Economic Studies, 1967)
Journal Article A Two-Level Constant-Elasticity-of-Substitution Production Function1 K. Sato K. Sato United Nations, New York Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 34, Issue 2, April 1967, Pages 201–218, https://doi.org/10.2307/2296809 Published: 01 April 1967